2013
DOI: 10.1593/neo.121954
|View full text |Cite
|
Sign up to set email alerts
|

Myeloprotection by Cytidine Deaminase Gene Transfer in Antileukemic Therapy

Abstract: Gene transfer of drug resistance (CTX-R) genes can be used to protect the hematopoietic system from the toxicity of anticancer chemotherapy and this concept recently has been proven by overexpression of a mutant O(6)-methylguaninemethyltransferase in the hematopoietic system of glioblastoma patients treated with temozolomide. Given its protection capacity against such relevant drugs as cytosine arabinoside (ara-C), gemcitabine, decitabine, or azacytidine and the highly hematopoiesis-specific toxicity profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…This applies specifically to myeloprotective gene therapy approaches employing the (over)expression of selectable drug-resistant genes in hematopoietic stem and progenitor cells (Lachmann et al, 2013), as here the exposure to cytotoxic and mutagenic agents and the proliferative stress exerted during the in vivo selection process associated with this approach represent additional genotoxic risk factors. Besides mutants of the dehydrofolate reductase enzyme or the multidrug resistance 1 (MDR1) gene, mutants of the O 6 -methylguanine DNA methyltransferase (MGMT) gene have been investigated with considerable success in this context.…”
Section: Introductionmentioning
confidence: 99%
“…This applies specifically to myeloprotective gene therapy approaches employing the (over)expression of selectable drug-resistant genes in hematopoietic stem and progenitor cells (Lachmann et al, 2013), as here the exposure to cytotoxic and mutagenic agents and the proliferative stress exerted during the in vivo selection process associated with this approach represent additional genotoxic risk factors. Besides mutants of the dehydrofolate reductase enzyme or the multidrug resistance 1 (MDR1) gene, mutants of the O 6 -methylguanine DNA methyltransferase (MGMT) gene have been investigated with considerable success in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance may be mediated by several factors, including low transporter levels and low deoxycytidine kinase (dCK) activity [1]. Furthermore, high human cytidine deaminase (hCDA) activity has been suggested to play an important role not only in drug resistance but also to protect cells from drug-mediated cytotoxicity (myeloprotection) [1,2]. Human CDA is an evolutionarily conserved enzyme involved in the pyrimidine salvage pathway and catalyzes the deamination of cytidine and deoxycytidine to uridine and deoxyuridine, respectively.…”
Section: Inactivation Of Chemotherapeutic Drugs By Cytidine Deaminasementioning
confidence: 99%
“…This could explain why some cytidine analogs have greater antitumor efficacy in vitro but limited effects in vivo, especially in liver cancer cells. Further evidence that high hCDA activity negatively impacts therapeutic outcome was found in leukemic cells, especially in those from patients who have relapsed after Ara-C therapy [1,2]. Mahfouz et al [4] also found that increased hCDA expression contributes to decreased cytidine analog half-life and likely also to poor outcomes following cytidine analog therapy.…”
Section: Inactivation Of Chemotherapeutic Drugs By Cytidine Deaminasementioning
confidence: 99%
See 1 more Smart Citation
“…Cells that overexpress CR deaminase show signs of drug resistance to ARA-C [24,25]. We detected an increased expression of CR deaminase in leukemic blasts after treatment with decitabine [19].…”
Section: Introductionmentioning
confidence: 99%